Nonlinear MHD simulation of core plasma collapse events in Wendelstein 7-X. (17th November 2021) - Suzuki, Yasuhiro; Futatani, Shimpei; Geiger, Joachim
Abstract: Three-dimensional nonlinear MHD simulations study the core collapse events observed in a stellarator experiment, Wendelstein 7-X. In the low magnetic shear configuration like the Wendelstein 7-X, the rotational transform profile is very sensitive to the toroidal current density. The 3D equilibrium with localized toroidal current density is studied. If the toroidal current density follows locally in the middle of the minor radius, the rotational transform is also changed locally. Sometimes, the magnetic topology changes due to appearing the magnetic island. A full three-dimensional nonlinear MHD code studies the nonlinear behaviors of the MHD instability. It was found that the following sequence. At first, the high- n ballooning-type mode structure appears in the plasma core, and then the mode linearly grows. The high- n ballooning modes nonlinearly couple and saturate. The mode structure changes to the low- n mode. The magnetic field structure becomes strongly stochastic into the plasma core due to the nonlinear coupling in that phase. Finally, the plasma pressure diffuses along the stochastic field lines, and then the core plasma pressure drops. This is a crucial result to interpret the core collapse event by strong nonlinear coupling.